A lexical-semantic analysis of Anthony Burgess's a clockwork orange - Solis, Mildred Alcano; Prof. Epistola, Nieves B. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1996)
This research paper explores the relationship between semantics and the lexical formations and processes in a literary text. It applies the lexical-semantic theory of Michael Cummings and Robert Simmons to the novel, A Clockwork Orange by Anthony Burgess. This paper likewise presents the lexical unions and colligations that are present in the Nadsat language, or the invented lexicon of burgess in the novel.
Thesis (Bachelor of Arts in English: Language Degree)--University of the Philippines Diliman